2020
DOI: 10.1055/s-0040-1715594
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transarterial Angiography with Embolization in Deciding Surgical Approach to Juvenile Nasopharyngeal Angiofibroma: A Step-Ladder Approach

Abstract: Objectives This study was aimed to understand the usefulness of transarterial angiography and embolization in management of juvenile nasopharyngeal angiofibroma (JNA) and to apply the information obtained to stage the disease, select appropriate surgical approach, predict intraoperative bleeding, and prognosticate the disease. Design This study represents a retrospective review of the patients of JNA with major focus on transarterial angiography and embolization findings and its clinical and surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…These improved radiography techniques have shown that 20% of the tumors showed intracranial extent. Definitive diagnosis was based on angiography which shows the feeding vessel and also aids in its embolization 17 . The characteristic angiographic appearance is a blush that appears on digital subtraction angiogram.…”
Section: Discussionmentioning
confidence: 99%
“…These improved radiography techniques have shown that 20% of the tumors showed intracranial extent. Definitive diagnosis was based on angiography which shows the feeding vessel and also aids in its embolization 17 . The characteristic angiographic appearance is a blush that appears on digital subtraction angiogram.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative arteriography can be safely and effectively used as an adjuvant surgery to embolize the feeding artery before JNA surgical resection [4] . In the present study, preoperative digital subtraction angiography showed contributing vessels from bilateral ECA and involvement of right ICA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the positive effects on blood loss and clarity during surgery, the angiography itself naturally depicts the relationships of the vascular architecture. This provides information about potential vascular inflows to be supplied, critical localizations of the tumor (affecting the vascular supply), and can thus also influence the choice of access route or other surgical steps [171]. While open surgical access and microscopic tumor removal via a Caldwell-Luc approach or (modified) midfacial degloving were more common a few years ago, the endonasal, endoscopic approach is preferred nowadays.…”
Section: Therapymentioning
confidence: 99%
“…Neben den positiven Effekten auf den Blutverlust und die Übersichtlichkeit während der Operation werden bei der Angiografie selbst natürlich auch die Verhältnisse der Gefäßarchitektur dargestellt. Dies gibt Auskunft über potentiell zu versorgende Gefäßzuflüsse, kritische Lokalisationen des Tumors (die Gefäßversorgung betreffend) und kann damit auch Einfluss haben auf die Wahl des Zugangswegs oder andere operative Schritte [171]. Während vor einigen Jahren noch offene chirurgische Zugangswege und eine mikroskopische Tumorentfernung über einen Mundvorhofzugang oder ein (modifiziertes) Midfacial degloving eher üblich waren, bevorzugt man heutzutage eher den endonasalen, endoskopischen Zugangsweg.…”
Section: Therapieunclassified